(untitled) (World Bulletin of Public Health, 2023)
to enquire the potentiality expenditure of physicist ultrasound and to determine cerebroplacental correspondence (CPR) in the prognostication of antagonistic perinatal after-effect characterized as Apgar reckoning < 7 at 1 minute